Differentiation of Pathogenic and Non-Pathogenic Burkholderias Using Rocket Immunoelectrophoresis - G. M. Napalkova; I. I. Korsakova; N. P. Khrapova; N. N. Piven'; L. V. Lomova; T. V. Bulatova (Проблемы особо опасных инфекций, 2010)
Demostrated is the possibility to differentiate virulent strains of melioidosis and glanders etiological agents from avirulent ones and closely related microorganisms according to the presence of the antigenic complex 8, using rocket immunoelectrophoresis with the serum containing antibodies to this complex.